EFFECT OF BRAND EQUITY AND CONSUMER PSYCHOLOGY ON THE PURCHASE DECISION OF GOODS - Hendri Mayanta Tarigan (CV. Radja Publika, 2022)
This study aims to answer three problems, namely: 1. Does Brand Equity have a significant effect on Purchase Decision? 2. Does Consumer Psychology have a significant effect on the decision to purchase goods? 3. Does Brand Equity and Consumer Psychology have a significant effect on Purchase Decision? Data collection was carried out using several sources and exploiting books, documents, the internet and other relevant sources. The research was analyzed using annotated bibliography analysis method. The results of the study show that Brand Equity has a significant influence on purchasing decisions. Consumer psychology also has a significant influence on purchasing decisions. Taken together, Brand Equity and Consumer Psychology have a significant effect on purchasing decisions. Among the two independent variables there is one variable that most dominantly influences consumer satisfaction, namely the Consumer Psychological variable